Increasing efficiency of plasma hardening by local cooling of surface by air with negative temperature - Bespalova, Alla; Lebedev, Vladimir; Frolenkova, Olga; Knysh, Alexey; Dashkovskaya, Olga; Fayzulina, Oksana (Eastern-European Journal of Enterprise Technologies, 2019)
The martensitic transformation interval of some hypoeutectoid, all eutectoid and all hypereutectoid steels covers to a large extent the region of negative temperatures. Due to the fact that the plasma hardening operation is carried out in workshops where the minimum temperature is +20 °С, the surface temperature of the part after plasma heating cannot reach negative values. Because of this, the temperature range of the martensitic transformation is not fully used and in the hardened structure there is a certain amount of austenite, which has not undergone martensitic transformation. This circumstance reduces the hardness of the hardened layer and often low tempering is required to convert residual austenite to tempered martensite, which lengthens and makes the heat treatment more expensive. Complete or almost complete martensitic transformation is possible if the surface heated by the plasma beam is immediately cooled to a negative temperature. It is shown that local cooling of the hardened surface to a temperature of –40 °C can be carried out by air using the Ranque-Hilsch tube, which significantly expands the possibilities of full hardening for eutectoid and hypereutectoid steels. The studies consisted in heating the surface with a plasma stream to a temperature of 750 °C and 900 °C. The temperature was changed by the plasma torch current and by changing the velocity of the plasma flow spot moving along the sample surface. The experiments were carried out on steels 45 (0.45 % C), U8 (0.8 % C) and U10 (1 % C). The study of the structures was carried out on a MIM-7 microscope with a video camera and with the image displayed on the screen. The approximate quantitative composition of austenite, martensite, and associated structures was determined by the areas on the screen. During plasma hardening of steel 45 from a temperature of 900 °C using the Ranque-Hilsch tube, there is practically no residual austenite in the structure. When hardening U8 steel, residual austenite is detected in a small amount. When hardening U10 steel, the amount of residual austenite is approximately 15 %. Local surface cooling allows high-quality hardening of steels of most grades, regardless of the carbon content.